Vasoreactive phenotype in children with pulmonary arterial hypertension and syncope. Issue 4 (10th October 2022) - Linder, Alexandra N.; Hsia, Jill; Krishnan, Sheila V.; Rosenzweig, Erika B.; Krishnan, Usha S.
Background: Syncope in Group 1 pulmonary arterial hypertension (PAH) is an independent predictor of poor prognosis in adults, but this is not well studied in children. We hypothesise that syncope in children with PAH often occurs in association with a reactive pulmonary vascular bed with sudden vasoconstriction in response to adverse stimuli. In the current study, we sought to determine the association of syncope with acute vasoresponsiveness and outcomes in children with Group 1 PAH. Methods: A retrospective chart review of children with PAH at a single pulmonary hypertension centre from 1 January 2005 to 31 October 2018 was performed. Data included demographics, symptoms, imaging, haemodynamics, and outcomes at baseline and follow-up. Results: 169 children had Group 1 PAH; 47 (28%) had syncope at presentation or follow-up. Children with significant shunts were excluded from the analysis. Children with syncope were older at diagnosis (7.5 versus 5.0 years; p=0.002) and had a higher incidence of chest pain (p=0.022) and fatigue (p=0.003). They had higher pulmonary vascular resistance at baseline (14.9 versus 9.1 WU·m 2 ; p=0.01). More children with syncope were vasoresponders to inhaled nitric oxide (33% versus 22%; p=0.08–NS). Children with syncope and acute vasoresponsiveness had the highest survival, and non-responders with syncope on medications had the worst long-term survival. Conclusions: Children with syncope had higher rates of vasoreactivity compared to those without. This suggests that in some children with PAH, syncope may simply reflect acute pulmonary vasoconstriction to an adverse stimulus. Larger prospective studies are warranted to further assess syncope as a marker for a vasoreactive phenotype with implications for treatment and long-term outcomes. Syncope in children with PAH may not portend adverse outcomes or classify them as high risk, especially if associated with vasoresponsiveness on haemodynamic testing. Vasoresponsiveness is associated with excellent survival even in the presence of syncope. https://bit.ly/3RsppkS